Development problems and strengthening health savings in terms of general education students academic institutions (Pedagogy of Higher and Secondary Education, 2013)
Dyshleva I. N. Development problems and strengthening health savings in terms of general education students academic institutions.The article reveals the state of development problems of implementation of health- technologies in the educational process in secondary institution. Made a deep analysis of the legal framework regarding organizational methods in the application of health- technology.
Keywords: Health; Health- technology; educational institution; primary school pupils